A Study of the Persistence of Mycobacterium bovis in the Environment under Natural Weather Conditions in Michigan, USA. (23rd March 2011) - Fine, Amanda E.; Bolin, Carole A.; Gardiner, Joseph C.; Kaneene, John B.
Abstract : Reisolation of Mycobacterium bovis from inoculated substrates was used to follow the persistence of viable M. bovis bacteria exposed to natural weather conditions over a 12-month period. Environmental factors were recorded continuously, and factors affecting M. bovis persistence (i.e., temperature, season, and substrate) were studied using survival analysis and Cox's proportional hazards regression. Persistence of M. bovis in the environment was significantly shorter in the spring/summer season, characterized by the highest average daily temperatures over the 12-month period. M. bovis persisted up to 88 days in soil, 58 days in water and hay, and 43 days on corn. These studies demonstrate that M. bovis bacteria persist long enough to represent a risk of exposure for cattle and/or wildlife and strengthen evidence that suggests cattle farm biosecurity and efforts to eliminate supplemental feeding of white-tailed deer will decrease the risk of bovine TB transmission among and between cattle and deer populations.